The Impact Of Corporate Social Responsibility On Companies Financial Performance - Ayu Asari; Nur Fitroten Dian Sari; Hwihanus Hwihanus (International Journal of Economics, Commerce, and Management, 2024)
This research discusses the impact of Corporate Social Responsibility (CSR) on company financial performance. Findings from various studies show a positive relationship between CSR and financial performance, where CSR activities influence profitability and company value. However, this relationship with renewable energy companies remains unclear, highlighting the need for further research in this area. Overall, investing in socially responsible initiatives may not always have a direct impact on firm value and performance, highlighting the complexity of the relationship between CSR and financial outcomes.